AODV And AOMDV Routing İn CDMA Based VMC Network - Devidas Gopal Lokhande, Devendra Ningappa Kyatanavar (International Journal of Advanced Science and Technology, 2020)
Next generation of mobile communication will include an adhoc network. An adhoc networks is prestigious, novel infrastructure less networks are very popular because of its easy deployment. It is a self-organizing network with self-configured capabilities called as dynamic topologies. Due to node mobility, routing is major issue in adhoc network and it play a vital role in data transmission from source to destination node also mobility factor affects the efficiency of the adhoc network. The adhoc network is said to be efficient if it transfers data with maximum packet delivery ratio, throughput, low overheads, minimum end to end delay and minimum jitter. In this paper, researcher studied the wireless multi hop, single path adhoc network as well as multi path adhoc network. The performances of different routing protocols are simulated using the Network Simulator NS2.34. This study will help in the researcher further to regulate the scenario performance of adhoc network and to design the perfect parameters to improve and enhance the performance of protocols and select the proper wireless network in the physical environment.